Effects of Nefopam on Postoperative Analgesia in Operating Room-Extubated Patients Undergoing Living Donor Liver Transplantation: A Propensity Score-Matched Analysis - Min Suk Chae; Jin-Oh Jeong; Kyung Kwan Lee; Wonwoo Jeong; Young Wook Moon; Ji Young Min (Life)
In patients undergoing living donor liver transplantation (LDLT) with immediate postoperative extubation in the operating room (OR), rapid recovery of consciousness and spontaneous ventilation are essential, requiring effective analgesia without compromising respiratory function. This study evaluated whether intraoperative nefopam administration improves early postoperative pain control and reduces opioid consumption in this physiologically distinct population. A retrospective cohort of 376 adult LDLT recipients who met the criteria for OR extubation was analyzed. After propensity score matching, 182 patients who received intraoperative nefopam were compared with 182 matched controls. Pain intensity was measured using the visual analog scale (VAS), and total fentanyl consumption and opioid-related complications were recorded over the first 24 h postoperatively. Nefopam administration was associated with significantly lower VAS scores during the first 12 h after surgery (p < 0.001) and reduced 24 h fentanyl consumption (53.2 ± 20.8 mL vs. 58.6 ± 27.5 mL, p = 0.035). No serious adverse effects related to nefopam were observed. The incidence of postoperative nausea and vomiting did not differ significantly between the groups. These findings indicate that nefopam offers effective early analgesia and an opioid-sparing effect in LDLT recipients undergoing OR extubation, suggesting its clinical utility as a component of multimodal analgesia in this high-risk group. Although the reduction in opioid use did not translate into a decreased incidence of opioid-related complications, the favorable safety profile and analgesic efficacy of nefopam support further investigation through prospective trials to define its role in enhanced recovery protocols for OR-extubated LDLT recipients.